REAKSI PASAR ATAS INFORMASI PENGUMUMAN PEMBENTUKAN KOMITE AUDIT - I Putu Sugiartha Sanjaya (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2007)
The role of the audit committee continues to be of importance to regulators. The New York Stock Exchange (NYSE) and the National Association of Securities Dealers (NASD) co-sponsored a Blue Ribbon Committee (BRC) to make recommendations for improving the effectiveness of the audit committee. In Indonesia, the Jakarta Stock Exchange (JSX) issued a regulation in 2001. The regulation emphasize all companies (which treaded publicly) must have audit committee. According to Millstein (1999), it is totally consistent that good corporate governance practice points to the audit committee as the focal point for improvement in financial statements. The objective of this study is to investigate whether the announcement of appointing audit committee is reacted by the market. Using a window of 7 days (three days before the announcement date and three days after the announcement dates), the result of this study is the market reacts to the announcement which explain audit committee is eligible to JSX’s standard and ineligible to JSX’s standard. Therefore, the result suggests that the information has information content.